A STUDY ON SOIL, FORAGE AND PLASMA LEAD LEVELS IN LACTATING COWS REARED IN SUBURB OF SARGODHA: TRANSPORT OF LEAD INTO MILK - Z. I. Khan; K. Ahmad; M. Sher; Z. Hayat; A. Hussain; A. Seidavi; Y. Rizwan (Journal of Animal and Plant Sciences, 2012)
To assess the transport of lead (Pb) in soil-plant-animal continuum, a study was conducted in a semi arid region of Punjab, Pakistan. Samples of soil, forage species, blood, and milk of lactating cows were taken four times during the study period and analyzed after wet digestion with atomic absorption spectrophotometry. The data were statistically analyzed and results showed that soil, forage, and plasma Pb remained unaffected (P<0.05) at different sampling periods. The maximum level of Pb in soil was at the 2nd sampling period (November) while, minimum concentration was observed at 4th sampling period during this study. Highest level of forage Pb was found at sampling period 1st (October) and lowest was at 3rd sampling period (December). Mean plasma Pb level was higher at 4th sampling time (January) and lower value at 3rd sampling period (December). The maximum level of milk Pb was observed during 4th interval while minimum level was at 3rd sampling period. Overall, results of the present study showed that accumulation of Pb in soil forage, plasma, and milk is very low that was non toxic for plants and animals and there is no warranted need of supplementation of animals with mineral mixture antagonistic or synergistic to Pb in this studied area.
Keywords: Lead; Soil; Forage; Plasma; Milk; Critical level.